Measuring the quality of health services provided at a Greek public hospital through patient satisfaction: Case study: the general hospital of Kavala - Vasiliki A. Georgiadou; Dimitrios Maditinos (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The aim of this study is to examine the quality of hospital services as perceived by patients in terms of patient satisfaction with services. Design/Methodology/Approach: A conceptual framework of quality of hospital services, developed by Padma et al. (2009), composed by eight quality dimensions, applied the performance measurement model (SERVPERF), was used for the approach. The Quality Score Tool was a two-part questionnaire that quantified patient satisfaction with benchmarks of the quality dimensions. In order to investigate the above model, the case study method was utilized. The survey was conducted in a public regional hospital. Findings: Five (5) quality dimensions (5Qs) have found having a significant impact on overall quality of service, measure of patient satisfaction in the hospital. These dimensions are on a hierarchical scale: "clinical care", "social responsibility", "staff quality", "infrastructure" and "Hospital reliability". Originality/Value: The results of this study can be used as a source of feedback to hospital management, meaning that they can essentially lead to improved adjustments or serve as a basis of process reengineering.
Keywords: 330; Hospital services; quality dimensions; patients satisfaction; hospital; SERVPERF